Geochemical survey of Levante Bay, Vulcano Island (Italy), a natural laboratory for the study of ocean acidification - BOATTA, Fulvio; GAGLIANO, Antonina Lisa; MILAZZO, Marco; PARELLO, Francesco; D'Alessandro, W; Liotta, M; Rodolfo Metalpa, R; Hall Spencer, JM (Marine Pollution Bulletin, 2013)
Shallow submarine gas vents in Levante Bay, Vulcano Island (Italy), emit around 3.6t CO2 per day providing a natural laboratory for the study of biogeochemical processes related to seabed CO2 leaks and ocean acidification. The main physico-chemical parameters (T, pH and Eh) were measured at more than 70 stations with 40 seawater samples were collected for chemical analyses. The main gas vent area had high concentrations of dissolved hydrothermal gases, low pH and negative redox values all of which returned to normal seawater values at distances of about 400m from the main vents. Much of the bay around the vents is corrosive to calcium carbonate; the north shore has a gradient in seawater carbonate chemistry that is well suited to studies of the effects of long-term increases in CO2 levels. This shoreline lacks toxic compounds (such as H2S) and has a gradient in carbonate saturation states.